Uncoupling of Vascular Nitric Oxide Synthase Caused by Intermittent Hypoxia. (20th October 2016) - Badran, Mohammad; Abuyassin, Bisher; Golbidi, Saeid; Ayas, Najib; Laher, Ismail
Abstract : Objective . Obstructive sleep apnea (OSA), characterized by chronic intermittent hypoxia (CIH), is often present in diabetic (DB) patients. Both conditions are associated with endothelial dysfunction and cardiovascular disease. We hypothesized that diabetic endothelial dysfunction is further compromised by CIH. Methods . Adult male diabetic (BKS.Cg- Dock7 m +/+ Lepr db /J) ( db/db ) mice (10 weeks old) and their heterozygote littermates were subjected to CIH or intermittent air (IA) for 8 weeks. Mice were separated into 4 groups: IA (intermittent air nondiabetic), IH (intermittent hypoxia nondiabetic), IADB (intermittent air diabetic), and IHDB (intermittent hypoxia diabetic) groups. Endothelium-dependent and endothelium-independent relaxation and modulation by basal nitric oxide (NO) were analyzed using wire myograph. Plasma 8-isoprostane, interleukin-6 (IL-6), and asymmetric dimethylarginine (ADMA) were measured using ELISA. Uncoupling of eNOS was measured using dihydroethidium (DHE) staining. Results . Endothelium-dependent vasodilation and basal NO production were significantly impaired in the IH and IADB group compared to IA group but was more pronounced in IHDB group. Levels of 8-isoprostane, IL-6, ADMA, and eNOS uncoupling were ≈2-fold higher in IH and IADB groups and were further increased in the IHDB group. Conclusion . Endothelial dysfunction is more pronounced in diabetic mice subjected to CIH compared to diabetic or CIH mice alone. Oxidative stress, ADMA, and eNOS uncoupling were exacerbated by CIH in diabetic mice.